Editorial - Thomas Wilson (Information Research: An International Electronic Journal)
The new, OJS-published version of the journal seems to be working well, although we lose some of the features of the original, such as the hand-made author and subject indexes, and rely instead on the internal search engine. Unfortunately, that means that, ultimately, when we have a more extensive collection of papers in the system, you will need to search both the old and the new system to find what you need. There’s nothing to be done about that, since continuing the handmade indexes was becoming much too time consuming.